Stereotyping across intersections of race and age: Racial stereotyping among White adults working with children - Priest, Naomi; Slopen, Natalie; Woolford, Susan; Philip, Jeny Tony; Singer, Dianne; Kauffman, Anna Daly; Mosely, Kathryn; Davis, Matthew; Ransome, Yusuf; Williams, David (PloS one, 2018)
This study examined the prevalence of racial/ethnic stereotypes among White adults who work or volunteer with children, and whether stereotyping of racial/ethnic groups varied towards different age groups. Participants were 1022 White adults who volunteer and/or work with children in the United States who completed a cross-sectional, online survey. Results indicate high proportions of adults who work or volunteer with children endorsed negative stereotypes towards Blacks and other ethnic minorities. Respondents were most likely to endorse negative stereotypes towards Blacks, and least likely towards Asians (relative to Whites). Moreover, endorsement of negative stereotypes by race was moderated by target age. Stereotypes were often lower towards young children but higher towards teens.